2023
DOI: 10.4235/agmr.22.0141
|View full text |Cite
|
Sign up to set email alerts
|

Potential Imaging Biomarkers of Cognitive Frailty

Abstract: Cognitive frailty (CF) is a state of impairment in both cognitive and motor functions. The concept of CF has been developed in several ways. However, it is difficult to identify consistent neuroimaging findings according to the application of the operational definition of different frailty models within the same concept, as well as the diversity of the concept itself of CF. This study aimed to review neuroimaging studies of CF and to determine suitable imaging biomarkers of CF.White matter abnormalities (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(63 reference statements)
0
1
0
1
Order By: Relevance
“…Several studies have demonstrated the association between hypertension, white matter lesions, and cognitive decline. 17,18) Cognitive decline and VLOSLP are more strongly associated with periventricular white matter hyperintensities than with subcortical brain infarctions on magnetic resonance imaging (MRI). 2,3,18) Additionally, several studies have suggested an association between estrogenic receptor polymorphisms and vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the association between hypertension, white matter lesions, and cognitive decline. 17,18) Cognitive decline and VLOSLP are more strongly associated with periventricular white matter hyperintensities than with subcortical brain infarctions on magnetic resonance imaging (MRI). 2,3,18) Additionally, several studies have suggested an association between estrogenic receptor polymorphisms and vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…De igual modo, predice la enfermedad cardiovascular [ 15 , 16 ]. Un estudio reciente muestra una posible asociación de este síndrome con anomalías de la sustancia blanca (hiperintensidad de la sustancia blanca y microsangrados), así como una disminución del volumen de la corteza cerebral/cerebelosa [ 17 ].…”
Section: Fragilidad Y Enfermedades Neurológicas: Implicación En La Pr...unclassified